Some special structures for the generalized nonlinear Schrodinger equation with nonlinear dispersion - İnç, Mustafa (Taylor & Francis Ltd, 2013)
This paper studies the generalized nonlinear Schrodinger equation with nonlinear dispersion in a detailed fashion. The ansatz method is employed to extract the compacton and solitary pattern solutions. Finally, the He's variational principle is applied to extract the traveling wave solutions of the NLS(2,1) equation with generalized evolution. The exponent of the wave function and the ratio of the two coefficients and in the NLS(m,n) are shown to determine the physical properties of the solitons.
Keywords: Exp-Function Method; Variational Approach; Physical Structures; Wave Solutions; Kp; Principle; Solitons